News Circulation in the Portuguese-Speaking Space: News Exchange between News Agencies of Brazil and Lusophone Africa - Juliana Costa Lisboa; Pedro Aguiar (Brazilian Journalism Research, 2017)
This paper addresses news exchange between Brazil and Portuguese-speaking countries of Africa, as carried out by each country’s national news agency. The main goal of this study is to understand how the flow of information is undertaken by these agencies. For this end, a quantitative and comparative survey was conducted on usage of texts from one agency by the other, by means of content analysis of cited material published on their respective websites, during the period of May 2016 to May 2017. In spite of important international events having taken place in Brazil during that time, the exchange between agencies was recorded as minimal. In order to analyze this exchange, we adopt theoretical perspectives from the political economy of news agencies (Boyd-Barrett, 1980) and of the circulation of news (Machado, 2008; Medina, 1998.) The paper applies the concept of network-territory to the analysis of news exchange and focuses on analyzing the structures of news production. The geocultural Lusophone sphere is understood here as a space of information circulation. The paper proposes a dialogue between Geographies of Communication and Journalism Studies.